1999
DOI: 10.1073/pnas.96.7.4028
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio cholerae O1 El Tor: Identification of a gene cluster required for the rugose colony type, exopolysaccharide production, chlorine resistance, and biofilm formation

Abstract: The rugose colony variant of Vibrio cholerae O1, biotype El Tor, is shown to produce an exopolysaccharide, EPS ETr , that confers chlorine resistance and biofilm-forming capacity. EPS ETr production requires a chromosomal locus, vps, that contains sequences homologous to carbohydrate biosynthesis genes of other bacterial species. Mutations within this locus yield chlorine-sensitive, smooth colony variants that are biofilm deficient. The biofilm-forming properties of EPS ETr may enable the survival of V. choler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

23
700
2
13

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 543 publications
(738 citation statements)
references
References 49 publications
23
700
2
13
Order By: Relevance
“…Both rugose and smooth cells grown at 30°C produce significantly more biofilm material than their counterpart rugose and smooth cells grown at 37°C. The observation that rugose cells produce more biofilm than do smooth cells is similar to what has been shown for rugose-expressing organisms (26,36).…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Both rugose and smooth cells grown at 30°C produce significantly more biofilm material than their counterpart rugose and smooth cells grown at 37°C. The observation that rugose cells produce more biofilm than do smooth cells is similar to what has been shown for rugose-expressing organisms (26,36).…”
Section: Discussionsupporting
confidence: 71%
“…The observations by microscopy of living rugose cells in this study showed that over time the cellular behavior of cells was to align themselves in chains, which then eventually formed laterally arranged aggregates or large multicellular cell masses. This description is markedly similar to what Yildiz and Schoolnik reported for V. cholerae O1 El Tor strains (36). However, one noted deviation in the results from these two studies is in the time frame that the aggregate formations occurred between these two Vibrio species.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…V. cholerae strains (O139 as well as O1) also produce another form of extracellular polysaccharide, designated VPS. In electron micrographs, VPS appears amorphous, filling the spaces between cells Yildiz and Schoolnik, 1999). Strains overproducing VPS form rugose colonies, exhibit enhanced biofilm formation, and are more resistant to environmental insult Wai et al, 1998;1999;Yildiz and Schoolnik, 1999;Hammer and Bassler, 2003;Zhu and Mekalanos, 2003).…”
Section: Discussionmentioning
confidence: 99%